(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
تعد اللغة وسيلة التواصل والتفاهم الأساسية بين البشر, إذ تسهم في بناء العلاقات الاجتماعية السليمة بين أفراد المجتمع الواحد من جهة, وفيما بين المجتمعات المختلفة من جهةً أخرى, بالإضافة لكونها تسهم في نقل الثقافة والتراث الإنساني من جيل إلى آخر, وفي تراكم المعارف والخبرات. يعتقد البعض أن الطفل يمارس اللعب إشباعاً لحاجات غريزية لديه, متجاهلين وظيفة اللعب وأهميته في اكتساب الطفل للغة المجتمع الذي يولد فيه, وطريقته للتأقلم معه, واكتساب خبراته وتنمية مهاراته, والتعبير عن مشاعره وأفكاره وانفعالاته. لذلك تركز الباحثة على بيان قدرة الألعاب اللغوية ودورها في إكساب الطفل المهارات اللازمة والمفاهيم الجديدة التي تثري لغته المكتسبة, وتساعده في دخول مرحلة التعليم الأساسي وفي جعبته الحد الأدنى اللازم من المعارف والمهارات من ناحية, والحد الأدنى من التهيئة النفسية للولوج في البيئة المدرسية من ناحية أخرى. لقد توصلت الباحثة إلى ضآلة قدرة الطريقة التقليدية المستخدمة عموماً في تعليم أطفال الرياض مقارنة بكفاءة طريقة استخدام الألعاب اللغوية وفعاليتها فيما يتعلق بإكساب الطفل المفاهيم اللغوية الضرورية وتعليمها. Language is a means of communication and understanding between the core of human beings, as it contributes to building sound social relations between members of the same society on the one hand, and among different communities on the other hand, as well as contributing in the transmission of culture and heritage from one generation to another, in the accumulation of knowledge and experience. Some believe that a child playing exercises, satisfying the needs of the instructive to him, ignoring the post play and its importance in acquisition of child language of the community which generates it, and own way of coping with, and to aging experience and develop skills, express, thoughts and emotions. Therefore, the researcher focused on the statement of the ability of language games and role in giving the necessary skills and new concepts that enrich the language experience and assist in entering the next phase, which is the stage of basic education, came with the minimum necessary knowledge and skills on the one hand, and minimum psychological preparation to enter the stage school. The researcher found that the traditional teaching methods are less effective than the modern methods that transport knowledge and skills.